PENERIMAAN TERHADAP KAUM DIFABEL: KAJIAN ALKITAB TERHADAP MATIUS 25:40 - Aihery, Joni (STT INDONESIA MANADO, 2024)
Abstract: People with disabilities is a term used to describe people who have different levels of physical and spiritual functioning or who experience disabilities. People with disabilities have different abilities as a result of the deficiencies or disabilities they suffer from. The condition of a person with a disability can be improved with assistive devices that make him able to carry out his activities as before. When Jesus comes a second time, He will judge people who do not care about people with disabilities. This research uses a qualitative literature approach, namely a literature review study by using the interpretation method, namely the reader’s critical interpretation (reader response). The research results show that people with disabilities really need attention and empathy from family, community, government and church in their respective capacities. Families need to provide sincere attention and affection to family members who experience disabilities. Society needs to accept people with disabilities in social groups regardless of physical appearance, ethnicity, nation, race, language and so on. The government can provide support through regulations that protect the rights of people with disabilities, as well as providing various services that can be accessed by them. Furthermore, the Church accepts people with disabilities as part of His creation. Abstrak: Penyandang disabilitas adalah istilah yang digunakan untuk menggambarkan orang yang memiliki perbedaan level fungsi jasmani dan rohani, atau yang mengalami disabilitas. Penyandang disabilitas memiliki kemampuan yang berbeda sebagai dampak dari kekurangan atau kecacatan yang diidapnya. Kondisi seorang penyandang disabilitas bisa diperbaiki dengan alat bantu yang membuatnya menjadi mampu melakukan aktivitasnya seperti semula. Ketika Yesus datang untuk yang kedua kalinya, Ia akan menghakimi orang-orang yang tidak mempedulikan kaum penyandang disabilitas. Penelitian ini menggunakan pendekatan secara kualitatif literatur, yaitu studi kajian pustaka. Dengan menggunakan metode tafsir, yakni tafsir kritik pembaca (reader respons). Hasil penelitian menunjukkan bahwa penyandang disabilitas sangat membutuhkan perhatian dan empaty dari keluarga, masyarakat, pemerintah dan gereja dalam kapasitasnya masing-masing. Keluarga perlu memberikan perhatian dan kasih sayang yang tulus pada anggota keluarga yang mengalami disabilitas. Masyarakat perlu menerima penyandang disabilitas dalam kelompok sosial tanpa melihat fisik, suku, bangsa, ras, bahasa dan lain sebagainya. Pemerintah dapat memberikan dukungannya melalui regulasi yang melindungi hak-hak penyandang disabilitas, juga menyediakan berbagai layanan yang dapat diakses oleh mereka. Selanjutnya, Gereja menerima penyandang disabilitas sebagai bagian dari ciptaan-Nya